Doktrin Akhir Zaman (Eskatologi) - Tatia Veni; Wildiana; Yermia Ekklesia; Sarmauli (CV Edujavare Publishing, 2025)
Eschatology, or the doctrine of the end times, is a branch of theology that discusses the final events in world history, including the second coming of Christ, the resurrection of the dead, the final judgment, and eternal life. This topic becomes the core of hope in the faith of many believers, while also giving rise to various interpretations and understandings. This article examines the concept of eschatology based on Biblical perspectives, from the promises in the Old Testament, the teachings of Jesus Christ, to the visions of the Apostle John in the book of Revelation. In addition, this article highlights the relevance of the doctrine of the end times for the lives of believers today, as well as the attitudes that should be taken while awaiting the fulfillment of God's promises.